Model Kewirausahaan Terpadu Berbasis Agribisnis dalam Meningkatkan Nilai Tambah Usaha Olahan Susu Lokal - Julizar Julizar; Azzahra Gunawan; Yulia Novita; Muhammad Lutfi Hamzah (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
To increase the added value of local dairy processing companies, this study investigates an integrated agribusiness-based entrepreneurship model. Lassy Dairy Farm, located in Nagari Lasi Tuo, Agam Regency, was the subject of the study, conducted using a descriptive qualitative approach with a case study design. Qualitative analysis was conducted after data were collected through documentation, in-depth interviews, and field observations. The results showed that combining dairy farming and milk processing activities into a single business unit can increase added value through diversification of processed products such as cheese and ice cream and improve supply chain efficiency. However, business development still faces obstacles related to formal partnership elements and expanding market access. According to this study, the competitiveness and sustainability of local dairy processing businesses can be improved through the implementation of an integrated agribusiness-based entrepreneurship model.